Determinan Penggunaan Kuesioner Pra Skrining Perkembangan Anak Pada Kader Posyandu - Endriyani Martina Yunus; Eka Safitri Yanti; Retno Imami (Citra Delima Scientific journal of Citra Internasional Institute, 2022)
The period of development of infants and children is a period of rapid growth and development and this determines their further development. Roesli (2009) in his research found that toddlers experience gross motor disorders as much as 31.2%, fine motor skills 14.3%, while those who experience language disorders are 19.1% and those who experience social personal disorders are 11.5%. Monitoring is very necessary to detect early deviations in child development. This study aims to determine the determinants of the use of pre-screening child development questionnaires for posyandu cadres in the working area of ​​the Benteng Bangka Tengah Health Center in 2021. This type of research is cross sectional, the type of data collection is total sampling. The use of the Pre-screening Questionnaire for Child Development in Posyandu Cadres in the Work Area of ​​the Benteng Bangka Tengah Health Center was 21 (35%) cadres. Determinants related to the use of the Pre-screening Questionnaire for Child Development in Posyandu Cadres in the Work Area of ​​the Benteng Bangka Tengah Health Center were the participation of cadres in KPSP training, the availability of facilities and infrastructure and the support of health workers. Benteng Health Center in order to facilitate KPSP training for cadres who have not been trained sothat the ability of cadres can increase so that the use of KPSP can be more evenly distributed.